Adapting Cloud Accounting As Creative Innovation And The Role Of Accountants In The Era Of Disruption - Pitria, Ni Gusti Ayu; Haliah, Haliah; Nirwana, Nirwana (JTI: Jurnal Teknik Industri, 2024)
Cloud accounting is a pivotal innovation in contemporary accounting, significantly altering how accountants operate. This article delves into the effects of cloud accounting on the accounting profession, examining its role in an era marked by technological upheaval and how accountants adapt to persist. It elucidates the transition prompted by cloud accounting from traditional task execution, such as transaction recording, to a more analytical approach focused on deep data analysis through process automation. Yet, this transition does not render the accountant's role redundant; rather, it underscores the ongoing necessity for accountants to refine their competencies. These include analytical prowess, data interpretation skills, engagement with emerging technologies, a commitment to ethical standards, and a mastery of strategic consulting. Additionally, the article points out the critical need for accountants to continuously advance their technological understanding, embracing tools like Power BI and programming languages such as SQL, to stay pertinent and effective amidst disruptive trends. By exploring both hurdles and prospects, the narrative posits accountants at the forefront of delivering insightful, value-added recommendations to businesses navigating the digital revolution. By presenting a comprehensive analysis of the evolving landscape, the article projects a nuanced perspective on the accountant's future role, advocating for readiness and adaptation to harness the benefits presented by cloud technology in this transformative period